Review of environmental monitoring in freshwater lakes using geospatial techniques (remote sensing and GIS) - Kamilia Kamaruzzaman; Siti Aekbal Salleh; Faezah Pardi; Muhamad Fuad Abdullah; Vladimir Foronda; Emerson L. Bergonio; Rahmawaty Rahmawaty (Geocarto International)
Human activities such as land-use change, and pollution pose a significant threat to the biodiversity and ecological services of freshwater lakes. This complex issue includes water quality degradation, natural habitat loss, and the introduction of unknown species. However, the complex interactions between debris, climate and lake environment remain poorly understood. Thus, this systematic review provides an academically comprehensive analysis of geospatial technologies for monitoring freshwater lakes. The review covers the time from 2018 to 2023. The reviews follow established methods and procedures for systematically identifying, evaluating, and testing the study literature. It seeks to address specific concerns in this area. The survey includes 318 papers, showing a significant increase in scholarly output throughout the defined period. Key findings reveal significant trends, including a 65% increase in publications between 2020 and 2021, driven by advancements in remote sensing and GIS applications. The study highlights the value of geospatial tools in identifying spatiotemporal variations in water quality, biodiversity and ecological health, emphasizing their role in guiding sustainable freshwater lake management. The research typically focuses on books published in English and includes open source to ensure the accessibility and transparency in the selection of source materials. The results not only highlight the significant increase in published works but also highlight the growing interest and dedication to understand environmental monitoring in freshwater lakes using geospatial technologies. This review focuses on the significance of geospatial technology in exploring the environmental degradation. It also emphasizes the benefits of utilizing systematic review procedures, which supports to enhance knowledge in this field of study.